Genus Lecithocera of Thailand. Part IV. Descriptions of three new species and notes on a little known species (Lepidoptera: Lecithoceridae) - Park, Kyu-Tek (Zootaxa, 2009)
This is the fourth of a series of studies on the genus Lecithocera Herrich-Schäffer from Thailand. In this contribution, three new species are described: L. montiatilis sp. nov., L. pakiaensis sp. nov., and L. cornutima sp. nov. Lecithocera anglijuxta Wu, described from a single male from China, is redescribed with details of the female genitalia and wing venation. Images of adults and the male and female genitalia of the four species are provided.